Green Recovery of Ukraine: Analysis of Game Narratives - Lysokolenko, Tetiana; Buturlina, Oksana (European Journal of Sustainable Development, 2025)
This article contributes to the discussion of the green growth narrative. It conducts a discourse analysis of materials presented by Ukrainian representatives at three conferences dedicated to Ukraine’s post-war recovery (Lugano 2022, London 2023, Berlin 2024). The aim of the research is to uncover the key aspects related to the topic of Ukraine’s green recovery in the analyzed documents. This study fills a gap in the analysis of various options for Ukraine’s post-war recovery and is aimed at stimulating discussions about the substantive aspect of Ukraine’s post-war recovery by demonstrating the different focuses of recovery in the presented documents. In this article, narratives are understood as stories about Ukraine’s green recovery after the war, forming a chain of statements to convey a vision of events. In the context of this study, the concept of Jean-François Lyotard’s game narratives is used as a framework for analyzing the key themes of Ukraine’s post-war green recovery. Keywords: green transition, Ukraine’s green recovery after the war, narrative, discourse, language game.